Bacterial and Fungal Toll-Like Receptor Activation Elicits Type I IFN Responses in Mast Cells - Kornstädt, Lisa; Pierre, Sandra; Weigert, Andreas; Ebersberger, Stefanie; Schäufele, Tim J.; Kolbinger, Anja; Schmid, Tobias; Cohnen, Jennifer; Thomas, Dominique; Ferreirós, Nerea; Brüne, Bernhard; Ebersberger, Ingo; et al. (Frontiers in Immunology, 2021)
Next to their role in IgE-mediated allergic diseases and in promoting inflammation, mast cells also have antiinflammatory functions. They release pro- as well as antiinflammatory mediators, depending on the biological setting. Here we aimed to better understand the role of mast cells during the resolution phase of a local inflammation induced with the Toll-like receptor (TLR)-2 agonist zymosan. Multiple sequential immunohistology combined with a statistical neighborhood analysis showed that during resolution of inflammation mast cells are located in a predominantly antiinflammatory microenvironment. Fittingly, cytokine screening of inflamed tissues showed a downregulation of antiinflammatory and pro-angiogenic cytokines in mast cell-deficient mice. In addition, macrophages in these mice had a decreased ability to phagocytose zymosan and neutrophils. mRNA sequencing using zymosan-induced bone marrow-derived mast cells (BMMC) revealed a strong type I interferon (IFN) response, which has been shown to enhance phagocytosis by macrophages. Bone marrow-derived mast cells released IFN-β in response to zymosan and lipopolysaccharides (LPS). Accordingly, IFN- was detected in mast cells during the resolution phase of the zymosan-induced inflammation. As previously described for macrophages the release of type I IFNs from mast cells depends on internalization and endosome acidification. In conclusion, mast cells produce IFN-β in response to non-viral TLR stimuli and have the potential to influence the phagocytosing activity of macrophages by a variety of antiinflammatory mediators.